Cell Type-Specific Regulation of Immunological Synapse Dynamics by B7 Ligand Recognition - Brzostek, Joanna; Gascoigne, Nicholas R. J.; Rybakin, Vasily (Frontiers in Immunology, 2016)
B7 proteins CD80 (B7-1) and CD86 (B7-2) are expressed on most antigen presenting cells and provide critical costimulatory or inhibitory input to T cells via their T-cell expressed receptors: CD28 and CTLA-4. CD28 is expressed on effector and regulatory T cells (Treg), and CD28-dependent signals are required for optimum activation of effector T cell functions. CD28 ligation on effector T cells leads to formation of distinct molecular patterns and induction of cytoskeletal rearrangements at the immunological synapse (IS). CD28 plays a critical role in recruitment of protein kinase C (PKC)-θ to the effector T cell IS. CTLA-4 is constitutively expressed on the surface of Tregs, but it is expressed on effector T cells only after activation. As CTLA-4 binds to B7 proteins with significantly higher affinity than CD28, B7 ligand recognition by cells expressing both receptors leads to displacement of CD28 and PKC-θ from the IS. In Tregs, B7 ligand recognition leads to recruitment of CTLA-4 and PKC-η to the IS. CTLA-4 plays a role in regulation of T effector and Treg IS stability and cell motility. Due to their important roles in regulating T cell-mediated responses, B7 receptors are emerging as important drug targets in oncology. In this review, we present an integrated summary of current knowledge about the role of B7 family receptor-ligand interactions in the regulation of spatial and temporal IS dynamics in effector and Tregs.